2002
DOI: 10.1093/cercor/12.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Sulcal Pattern Asymmetry and Local Cortical Surface Gray Matter Distribution In Vivo: Maturation in Perisylvian Cortices

Abstract: Previous in vivo morphometric studies of human brain maturation between childhood and young adulthood have revealed a spatial and temporal pattern of progressive brain changes that is consistent with the post mortem cytoarchitectonic and cognitive developmental literatures. In this study, we mapped age differences in structural asymmetries at the cortical surface in groups of normally developing children (7-11 years), adolescents (12-16 years) and young adults (23-30 years) using novel surface-based mesh model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(170 citation statements)
references
References 42 publications
10
159
1
Order By: Relevance
“…3, right) as asymmetric. This confirms results by Sowell et al (2002), who found the most prominent area of asymmetry in adult subjects in the inferior prefrontal cortex. Memory-related cortices (e.g., the parahippocampal gyrus and the retrosplenical cortex, Table 3) and gross white matter bundles (e.g., the corona radiata and the knee region of the internal capsule) become more asymmetric with age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3, right) as asymmetric. This confirms results by Sowell et al (2002), who found the most prominent area of asymmetry in adult subjects in the inferior prefrontal cortex. Memory-related cortices (e.g., the parahippocampal gyrus and the retrosplenical cortex, Table 3) and gross white matter bundles (e.g., the corona radiata and the knee region of the internal capsule) become more asymmetric with age.…”
Section: Discussionsupporting
confidence: 92%
“…Alternative, surface-based approaches characterize gyral and sulcal pattern variations across subjects in order to remove confounds of cortical surface variability (Thompson et al, 1997(Thompson et al, , 1998Sowell et al, 2001Sowell et al, , 2002Narr et al, 2001a,b). Both approaches retain information about morphometric measures from individual subjects and facilitate the detection of fine structural differences in brain anatomy (e.g., local shape variation, local gray matter concentration, and asymmetry).…”
Section: Introductionmentioning
confidence: 99%
“…color or object processing) tasks is not conclusive, as it seems likely that even cortical territories known to be distinct would be found to overlap with this method. This is especially true when the method is applied across different groups of subjects, although individual sulci are known to vary at least up to 1 cm (Sowell et al, 2002;Thompson et al, 1996).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Several studies have measured or mapped brain changes in children and adolescents scanned repeatedly during childhood and adolescence (Chung et al, 2001a,b;Giedd et al, 1999;Gogtay et al, 2004;Sowell et al, 1999aSowell et al, ,b, 2001Sowell et al, , 2002aSowell et al, ,b, 2004aThompson et al, 2000aThompson et al, ,b, 2001a. The dynamics of brain change across the adult human life span are highly nonlinear (Jernigan et al, 1991;Sowell et al, 2003a,b).…”
Section: Developmentmentioning
confidence: 99%